2020
DOI: 10.1007/s13187-020-01919-7
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Medical Students Towards Oncology: Results from a Pilot Multi-institutional Mentorship Programme

Abstract: The mounting global cancer burden has generated an increasing demand for oncologists to join the workforce. Yet, students report limited oncology exposure in undergraduate medical curricula, while undergraduate oncology mentorships remain underutilised. We established an undergraduate oncology society–led mentorship programme aimed at medical students across several UK universities to increase medical student oncology exposure. We electronically recruited and paired oncologist mentors and medical student mente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Using this strong network, BONUS has implemented a platform to enable local oncology events to be advertised nationwide and for our national events to be advertised at local universities. Mentoring in oncology has been shown to increase interest in the field [6,16] and BONUS has developed a national mentorship scheme, which launched in 2021. The scheme is based on three pilot programmes [10,16,17], including one virtual scheme.…”
Section: Oncology Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this strong network, BONUS has implemented a platform to enable local oncology events to be advertised nationwide and for our national events to be advertised at local universities. Mentoring in oncology has been shown to increase interest in the field [6,16] and BONUS has developed a national mentorship scheme, which launched in 2021. The scheme is based on three pilot programmes [10,16,17], including one virtual scheme.…”
Section: Oncology Networkmentioning
confidence: 99%
“…Mentoring in oncology has been shown to increase interest in the field [6,16] and BONUS has developed a national mentorship scheme, which launched in 2021. The scheme is based on three pilot programmes [10,16,17], including one virtual scheme. The scheme, spanning a period of 6 months, pairs mentors (consultants or specialty registrars) with mentees (medical students or junior doctors) based on location and speciality of interest.…”
Section: Oncology Networkmentioning
confidence: 99%
“…Survey answers were in the form of a 5-point Likert scale: strongly disagree, 1 disagree, 2 neither agree nor disagree, 3 agree 4 and strongly agree. 5 A follow-up survey was conducted at the conclusion of the program. Due to the COVID-19 pandemic, the ASPIRE program transitioned from face-to-face (2019) to online sessions (2020).…”
mentioning
confidence: 99%
“…Particularly too as guidance through resource provision has previously been identified to empower participants in their learning. 5 At the same time, face-to-face lectures are particularly popular amongst students learning new material. 6 However, Harris et al have shown frameworks to be efficacious and more sustainable when used with other techniques and their importance adequately promoted amongst students.…”
mentioning
confidence: 99%
See 1 more Smart Citation